Monetary Response To The Global Economic Crisis In A Small, Open Economy With Fixed Ex-change Rate - The Case Of The Republic Of Macedonia - Trenovski, Borce; Tashevska, Biljana (Center for Economic Analysis, 2015)
The global economic crisis imposed one of the most significant challenges for the conduct of monetary policy,which forced monetary authorities throughout the world to reach the limits of their conventional instruments andimplement new sets of measures for exit of the crisis. The situation created by the global crisis presented anespecially interesting challenge, not only for developed economies, but also for small economies with fixedexchange rate, which were supposed to survive this economic storm without having their anchors blown awayby the “strong wind”. The Macedonian economy is an example of a small open economy, highly intergrated intrade, which for a longer period maintains the fixed exchange rate as a best suited monetary regime for sus-taining a stable macroeconomic environment. The monetary authority (NBRM) successfully responded to thechallenges of the global economic crisis despite the specific characteristics of the Macedonian economy andthe monetary regime which limits its response. Thus, we found a special challenge in elaborating and analyz-ing the response of the Macedonian monetary authority to the global crisis. The elaboration of the undertakenmeasures can be a solid ground and a guide for the creation of monetary policy in small open economies witha fixed exchange rate. The paper is structured as follows: the first section elaborates the transmission of the economic crisis; the sec-ond section focuses on the general picture of the monetary resonse; the third section analyses the monetaryauthority’s response at the beginning of the global crisis, when it reacted with a monetary tightening; the fourthsection elaborates the monetary policy response in the peak of the crisis, characterized by monetary relaxation;the fifth section presents the macroprudential measures implemented for fighting the crisis and the last sectiongives summarized conclusions about the monetary response to the crisis.
Keywords: monetary policy, global crisis, monetary measures, macroprudential policy